Kompos Organik An-Aerob Berkatalisator Alami Muntingia Calabura. L Sebagai Alternatif Solusi Peningkatan Kualitas Lahan Non-Potensial - Fahmi Asyrofi Nur Fauzi; Ahmad Azis Rosyidi; Nur Rohman, Muhammad Fauzi; Widayoko, Agus (SMA Trensains Muhammadiyah Sragen, 2022)
The purpose of this study was to determine the manufacturing process and the advantages of organic an-aerobic organic compost with natural catalyst Muntingia Calabura .L as an alternative solution to non-potential soil problems. This type of research is descriptive research with a quantitative approach. The focus of the research description is on the process of making compost made from cherry leaves (Muntingia Calabura .L) and comparing experimental data between compost made from cherry leaves and compost made from mixed leaves while controlling the starter. Data was collected by experiment and observation. The data obtained were analyzed by descriptive statistics. The variables that will be observed in composting are changes in smell, and the time it takes to make compost. The results showed that the daily temperature of cherry leaf compost was higher than that of mixed leaf compost, the smell of fermentation was maintained from the second day to the 30th day and the composting time of cherry leaf compost was 9-10 days faster than compost made from mixed leaves. Suggestions for further research is the need for measuring pH in composting, whether the acidic environment has an influence on composting with an-aerobic process. Keywords: anaerobic, cherry, compost